ANALISIS PROFITABILITAS DAN NILAI TAMBAH USAHA INDUSTRI PANGAN PRODUK CARANG MAS DI KABUPATEN MAGETAN - Wati, Ratrika; Darsono, Darsono; Antriyandarti, Ernoiz (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2021)
Carang mas is a type of snack made from sweet potato. This study aims to determine the cost structure, the profitability and added value of processing sweet potatoes into carang mas by using descriptive and analytical methods. The location is chosen by applying purposive sampling, and sample is selected by census method. Data collection techniques used observation, interview, and note-taking. Data analysis methods used: (1) Cost; (2) Revenue; (3) Break event Point; (4) Profitability; and (5) Added Value. The results showed that the average variable cost is IDR 32.090.664,88 production/month and the average fixed cost is IDR 436.482,42 production/month. The average total cost spent is IDR 32,527,147.30 productions/month. The average revenue of the machete industry is IDR 39.486.431,28 production/month. The amount of Break Event Point units is 627,42 packages per month, while the of Break Event Point sales is IDR 2.330.414,69 production/month. The Margin Of Safety value is 94,10% and the value of the Marginal Income Ratio is 18,73%, so the profitability value in the business of carang mas is 17,62%. Processing of potato into carang mas generates the gross added value of IDR 1.400,75 per kilogram, while the net value added amounts to IDR 1.169,80 per kilogram. The average labor used in its industry is five people.